Extraction of fuzzy rules using deterministic annealing integrated with [epsilon]-insensitive learning - Czabański, Robert (Zielona Góra: Uniwersytet Zielonogórski)
A new method of parameter estimation for an artificial neural network inference system based on a logical interpretation of fuzzy if-then rules (ANBLIR) is presented.
Keywords: fuzzy systems; neural networks; neuro-fuzzy systems; rules extraction; deterministic annealing